WRITTEN PORTUGUESE LANGUAGE AS SECOND LANGUAGE - Izabelly C. dos Santos Brayner; Antonio H. Coutelo de Moraes; Wanilda Maria Alves Cavalcanti (Diacrítica, 2019)
Writing plays a fundamental role in active participation in society, since it facilitates access to knowledge. In the case of the deaf people involved in our research, this modality represents a second language, placing them in a bilingual perspective - an educational approach that guides professionals in the education of this linguistic minority. The objective of this research was to analyze the written productions of the deaf students of the Group of Studies and Practices of Language for the Deaf, Catholic University of Pernambuco, aiming at a better understanding of the obstacles to textual production learning in L2. Authors such as Brochado (2003), Lacerda (1998), Pereira and Karnopp (2012), Quadros (2004), among others, will be brought into the theoretical foundation, which will serve as a basis for discussions. The methodology adopted was qualitative descriptive. The data indicated the subjects are in stages I and II of the interlanguage, no subjects were identified in stage III. We conclude that investment is still necessary in researches that seek strategies to strengthen L2 writing by deaf people, as well as the acquisition of knowledge available mostly in written Portuguese language in several educational resources.